A practical approach to reduce interference due to in-source collision-induced dissociation of acylglucuronides in LC––MS/MS. (August 2011) - Mess, Jean-Nicholas; Béérubéé, Eugéénie-Raphaelle; Furtado, Milton; Garofolo, Fabio
Background: In LC––MS/MS, glucuronide conjugated metabolites may convert back to the parent drug due to in-source collision-induced dissociation (CID).Results: During the bioanalysis of naproxen, it was noticed that naproxen acylglucuronide exhibited intense in-source CID to the naproxen [M+H] + ion under positive ESI. However, no in-source CID of the acylglucuronide to the naproxen [M+NH4 ] + adduct was observed. Furthermore, absolutely no in-source CID was detected under negative ESI. This phenomenon was not only observed for naproxen acylglucuronide but for eight other acylglucuronides compounds.Conclusion: We have shown that monitoring the parent drug [M-H] - or [M+NH4 ] + whenever possible could be an easy approach used by bioanalytical scientists to minimize the impact of in-source CID of acylglucuronides to the parent drug.